The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/s1525-1578(10)60526-0
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Pitfalls in HNPCC Screening by Microsatellite Analysis and Immunohistochemistry

Abstract: Hereditary non-polyposis colorectal cancer (HNPCC) accounts for approximately 2 to 4% of the total colorectal cancer burden. For economic reasons a diagnostic "stepladder" is recommended. After evaluation of the family history , diagnostic microsatellite instability (MSI) analysis has found its place as a valuable screening tool for HNPCC. Immunohistochemical analysis can help to pinpoint the affected gene. The detection of a mutation in one of the responsible mismatch repair gene confirmed the diagnosis HNPCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 33 publications
0
44
0
1
Order By: Relevance
“…In addition, IHC allows for the specific identification of the defective MMR protein(s). However, IHC can be intact in MSI-H tumors with germline mutations when the specific mutation(s) does not disrupt antibody-reactive epitope, 19 and IHC might not be the ideal method for detecting EMC in treated patients, as chemoradiation can reduce MMR protein expression in otherwise MSS tumors. 20 There are several possible mechanisms underlying the difference in MSI profiles seen in MSI-H EMCs and CRCs that, in part, may be attributable to differences in the biology of the two different types of epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IHC allows for the specific identification of the defective MMR protein(s). However, IHC can be intact in MSI-H tumors with germline mutations when the specific mutation(s) does not disrupt antibody-reactive epitope, 19 and IHC might not be the ideal method for detecting EMC in treated patients, as chemoradiation can reduce MMR protein expression in otherwise MSS tumors. 20 There are several possible mechanisms underlying the difference in MSI profiles seen in MSI-H EMCs and CRCs that, in part, may be attributable to differences in the biology of the two different types of epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…There is room for improvement, however, as it is likely that none of the studies under review used the most sophisticated MSI test now possible for identifying CRC patients with Lynch syndrome. Methodological studies have shown the importance of laser microdissection, 21,25 the proportion of tumor tissue tested, and the number of cells tested. 25,26 Other studies have provided ways to improve testing of poor quality samples.…”
Section: How Can Clinical Sensitivity Of Msi Testing Be Improved?mentioning
confidence: 99%
“…4 Therefore, microsatellite analysis is commonly used as the first diagnostic screening test for LS. 18 Microsatellite instability testing involves amplification of a standardised panel of DNA markers (Bethesda/National Institutes of Health markers), although laboratories may use 10 or more markers and, more recently, a commercially available kit based on five mononucleotide markers has become popular as mononucleotide microsatellites may be the most sensitive markers for use in detecting MSI. 4 The process involves microdissection of tumour tissue, followed by extraction of DNA which is then amplified and run on a DNA fragment length analyser.…”
Section: Microsatellite Instability Testingmentioning
confidence: 99%